Investigation and optimization of solidification performance of a triplex-tube latent heat thermal energy storage system by rotational mechanism - Huang, Xinyu; Li, Fangfei; Xiao, Tian; Guo, Junfei; Wang, Fan; Gao, Xinyu; Yang, Xiaohu; He, Ya-Ling (Applied energy, 2023)
•The rotating mechanism is applied to a triplex-tube LHTES system.•The effect of rotation on heat transfer during solidification of PCM is studied.•Response surface method is used to optimize the solidification performance of LHTES.•The fluid-structure coupling functions of solidification time for each parameter are fitted. In this paper, the rotation mechanism is applied to a triplex-tube latent heat thermal energy storage system for the first time. Numerical simulation is used to study the effect of rotation on the solidification performance of this system, and the accuracy of the numerical model is verified experimentally. Firstly, the evolution of the liquid phase, the total amount of heat energy released, and the rate of heat energy released in the solidification process of the thermal energy storage system without rotation and at different rotational speeds are compared and analyzed. It is found that the solidification time of the system at 1 rpm is reduced by 83.85 % and the heat release rate is 4.98 times higher than that at the no-rotation state. It shows that the incorporation of a rotational mechanism can effectively reduce the solidification time and increase the heat release rate of the system. Then, the internal dynamic temperature/flow rate response is used to investigate the change in the heat transfer mode of the solidification process by the addition of rotation and the improvement of the phenomenon of difficult solidification zones, which improved the internal temperature uniformity and thus the solidification behavior. By response surface method, the geometric factors of the heat storage system (fin length, fin width, fin angle) are analyzed by multiple factors. The function of the optimized target (solidification time) on each variable is fitted, and it is found that the fin length had the most significant effect on the optimized target. Finally, the effect of relevant physical parameters on the solidification process and heat release of the thermal energy storage system is investigated. To ensure low solidification time and high heat release rate, this study recommends that the temperature difference between phase change material and tube wall is higher than 25 K. This paper also proves the feasibility and superiority of copper fin/tube wall material.